PENGAWASAN PENGELOLAAN DANA DESA OLEH BADAN PERMUSWARATAN DESA DALAM PELAKSANAAN PASAL 31 HURUF C PERMENDAGRI NOMOR 110 TAHUN 2016 (Studi di Desa Karangrejo, Kecamatan Ngasem,Kabupaten Kediri) - Firdaus Jonathan (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
Firdaus Jonathan, Agus Yulianto, SH., MH., Lutfi Effendi, SH., M.Hum. Fakultas Hukum Universitas Brawijaya Email: frdaus jonathan@gmail.com   ABSTRAK Penelitian ini mengambil permasalahan mengenai: (1) Bagaimana pengawasab pengelolaan dana desa oleh Badan Permusyawratan Desa Karangrejo? (2) Apa kendala dan upaya dalam pengawasab pengelolaan dana desa oleh Badan Permusyawaratan Desa Karangrejo?Menggunakan metode yuridis empiris dengan pendekatan yuridis sosiologis. Penelitian ini menggunakan teknik analisis data deskriptif kualitatif. Dengan teknik itu peneliti mengola data primer dan data sekunder hasil penelitian di lapang dibandingkan dengan peraturan perundang – undangan. Tahap terakhir adalah memberikan solusi dan mengambil kesimpulan. Bahwa Badan Permusyawaratan Desa adalah sebuah lembaga perwujudan demokrasi dalam penyelenggaraan pemerintahan desa, BPD mempunyai fungsi sebagaimana yang diatur dalam. Kata Kunci: Pelaksanaan, Badan Permusyawaratan Desa   ABSTRACT This study takes the issue related to: (1) How is the supervision of village fund management by Karangrejo Village Consultative Body? (2) What are the obstacles and efforts in supervising the village fund management by the Karangrejo Village Consultative Body? The author used an empirical legal method with a sociological juridical approach. This study uses qualitative descriptive research as a technique of data analysis. By using this technique, the author uses primary and secondary data from the results of field studies, comparing with legislations. The last step is to provide solutions and draw conclusions. The Village Consultative Body is an institution for realizing democracy in order to implement village governance. The Village Consultative Body has a function which is stipulated in Article 31 of Permendagri Number 110 of 2016 to discuss and agree on Draft Village Regulation along with the Village Head; obtain and share their aspirations of the Village community; and supervise the performance of the Village Head. The implementation of village government in Karangrejo village, Ngasem Sub-district, Kediri Regency related to the functions of the Village Consultative Body as supervisor of village fund management in the context of supervision of village head performance still cannot be implemented well. Based on the that problem, the author raised a research entitled Supervision of Village Fund Management Conducted by Village Consultative Body in Implementing Article 31 letter c of Regulation of the Minister of Home Affairs (Permendagri) Number 110 of 2016 on Village Consultative Body Keywords: Supervision of Village Fund Management, Village Consultative Body